Answer:122
Step-by-step explanation:
Answer:
-4
Step-by-step explanation:
Given function
f(x) = -2x² + 3x - 4
Comparing with ax² + bx + c We get
c = - 4
Hope it will help :)❤
Answer:
b=3, y=6
Step-by-step explanation:
Label the 2 equations:
2b +6y= 42 -----(1)
2b +4y= 30 -----(2)
(1) -(2):
(2b +6y) -(2b +4y)= 42 -30
2b +6y -2b -4y= 12
2y= 12
y= 12 ÷2 <em>(</em><em>÷</em><em>2</em><em> </em><em>on</em><em> </em><em>both</em><em> </em><em>sides</em><em>)</em>
y= 6
Susbt. y=6 into (2):
2b +4(6)= 30
2b +24=30
2b= 30 -24 <em>(</em><em>-24</em><em> </em><em>on</em><em> </em><em>b</em><em>o</em><em>t</em><em>h</em><em> </em><em>sides</em><em>)</em>
2b= 6
b= 6 ÷2
b= 3